When a Nontuberculous Mycobacterial Infection Reveals an Error of Immunity: A Single Center's Experience. Issue 5 (8th April 2022) - Morreale, Alessia; Dotta, Laura; Vairo, Donatella; Bazzana, Tullia; Lougaris, Vassilios; Soresina, Annarosa; Plebani, Alessandro; Giliani, Silvia Clara; Porta, Fulvio; Matteelli, Alberto; Redaelli De Zinis, Luca Oscar; Badolato, Raffaele
Abstract : We present an algorithm that may be applied in case of a diagnosis of pediatric nontuberculous mycobacterial disease to identify the patients who may require an immunologic assessment to discover a possible underlying immune system defect predisposing to their nontuberculous mycobacterial infections.